Les camps d’internement du sud en Algérie (1991-1995). Contextualisation et enjeux - Saphia Arezki (L’Année du Maghreb)
This article aims to shed light on a part of Algeria’s contemporary history largely unknown: the internment of thousands of men in the Sahara from 1991 to 1995. This historical sequence has never been the subject of historical research while contemporary witnesses agree that it constitutes a turning point and played a key role in rallying numerous Algerians to the maquis. It is thus a question of recalling the context in which these camps were open, explaining the decision-making process which led to their establishment while sketching a first collective portrait of the men who were sent there. In doing so, this article hopes to contribute to writing the history of the Algerian Civil War, many aspects of which are still unknown.